Ash Formation and Associated Interactions during Co-Combustion of Wheat Straw and Sewage Sludge - Yingnan Shan; Hongfang Zhou; Changdong Sheng (Energies, 2024)
The aim of the present work was to investigate ash formation and associated interactions during the pulverized fuel co-combustion of biomass fuels. Combustion experiments were carried out with narrowly sized wheat straw (WS), sewage sludge (SS), and their blends in a drop tube furnace at 1100 °C and 1300 °C. The resulting residual ash and fine particulate matter (PM10) were characterized with various analyses. It was observed that co-combustion influences size distributions of the residual ash particles and generally generates larger residual ash particles close to those of SS combustion. The interaction of K capture by minerals enhances the melting and consequently increases the production of large and melting ash particles during co-combustion. It was found that blending SS with WS has not only the positive interaction of K capture by minerals from SS ash to significantly reduce submicron ash formation, but also the positive interaction of transforming alkali chlorides into alkali sulfates to reduce the corrosiveness of submicron ash particles. Co-combustion of SS with WS can also reduce the presence of alkali chloride at PM1–10, lowering the propensities of deposition and corrosion of the fine residual ash particles.